2013
DOI: 10.1016/s0187-6236(13)71086-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine in the stratosphere

Abstract: Este artículo reseña varios aspectos de los compuestos clorados presentes en la estratosfera, que incluyen tanto su papel como agentes químicos como su función de trazadores de los procesos dinámicos. En la estratosfera, el cloro reactivo se libera a partir de los clorofluorocarbonos y otros gases orgánicos que contienen cloro. La mayor parte del cloro reactivo se convierte en compuestos inertes que almacenan cloro, como ClONO 2 y HCl. La reactivación del cloro estratosférico ocurre principalmente por reaccion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 429 publications
0
9
0
Order By: Relevance
“…The increase of perchlorate in Antarctic snow since the late 1970s coincides with the timing of significant increases of chlorine in the stratosphere [World Meteorological Organization, 2014]. Anthropogenic emissions of chlorine compounds-including chlorofluorcarbons (CFCs)-during the latter half of the twentieth century [Montzka et al, 1999;Schauffler et al, 2003;Von Clarmann, 2013] has been identified as the key factor in increased levels of chlorine in the stratosphere. The amount of chlorine in the stratosphere may be represented by equivalent effective stratospheric chlorine (EESC)-a parameter based on emission calculations and ozone depletion potentials [Newman et al, 2007].…”
Section: 1002/2016gl070203mentioning
confidence: 99%
“…The increase of perchlorate in Antarctic snow since the late 1970s coincides with the timing of significant increases of chlorine in the stratosphere [World Meteorological Organization, 2014]. Anthropogenic emissions of chlorine compounds-including chlorofluorcarbons (CFCs)-during the latter half of the twentieth century [Montzka et al, 1999;Schauffler et al, 2003;Von Clarmann, 2013] has been identified as the key factor in increased levels of chlorine in the stratosphere. The amount of chlorine in the stratosphere may be represented by equivalent effective stratospheric chlorine (EESC)-a parameter based on emission calculations and ozone depletion potentials [Newman et al, 2007].…”
Section: 1002/2016gl070203mentioning
confidence: 99%
“…Deactivation of active chlorine into ClONO 2 has not been at the observable expense of HCl reformation rate (in both 2002 and 2019). Such fast premature deactivation of active chlorine into ClONO 2 early in the Antarctic season is more akin to that seen in the warmer, and less denitrified, Arctic spring stratosphere (Douglass et al, 1995;Santee et al, 1995;Rex et al, 1997;Von Clarmann, 2013). As we will see in section 5.4 the rapid rise in ClONO 2 early in the springtime correlates with an equally fast deactivation of ClO and synchronized with an increase in temperature and NO 2 .…”
Section: Hydrogen Chloride (Hcl) and Chlorine Nitrate (Clono 2 )mentioning
confidence: 67%
“…Panel a) illustrates the composite mean ClO August through late September). This is followed by a large reduction in ClO mixing ratio, due to deactivation of chlorine with the reformation of its reservoirs (von Clarmann, 2013). Note that values below zero are a result of the known negative bias in MLS ClO.…”
Section: Mls Clo Observationsmentioning
confidence: 98%